Global, regional, and national burdens of five main digestive system cancers in adolescents and young adults from 1990 to 2021 based on the Global Burden of Disease Study 2021: A cross-sectional study - Mengjia Zhu; Xinjie Wang; Dian Zhang; Angli Chen; Weiling Hu (PLoS ONE, 2025)
Objective To evaluate the burden and trends of digestive system cancers in adolescents and young adults (AYAs) globally between 1990 and 2021. Methods Data were extracted from the Global Burden of Diseases, Injuries, and Risk Factors Study (1990–2021). We analyzed global, regional, and national disease burdens by calculating the age-standardized incidence (ASIR), mortality (ASMR), and disability-adjusted life years (DALYs) for AYAs. Joinpoint regression calculate the average annual percentage change (AAPC) in incidence, mortality, and DALYs for digestive system cancers in the AYAs. Decomposition analysis illustrate the impact of epidemiological changes, population growth, and population aging on the disease burden. Results Globally, the ASIR (AAPC: 0.37) of AYAs with colorectal cancer (CRC) showed an increasing trend, whereas the ASIR of AYAs with esophageal cancer (EC), gastric cancer (GC), pancreatic cancer (PC), and liver cancer (LC) showed a decreasing trend. The ASMR and age-standardized rates (ASR) of DALYs for all five types of digestive system cancers in AYAs also showed a decreasing trend. By gender, the ASIR for males has increased with an AAPC of 0.84. For the other four types of digestive system cancers in AYAs, both males and females showed a decreasing trend. For AYAs with CRC, the fastest increase in ASIR (AAPC: 0.73) was observed in the 30–34 age group. Regarding SDI regions, we found that the ASIR of AYAs with CRC increased in all five Social Demographic Index (SDI) regions. For AYAs with PC, the burden was increased in low and low-middle SDI. In the AYAs with LC, the ASIR also increased in low-middle SDI. For AYAs with EC and GC, both showed a decreasing trend across all five SDI regions. Conclusion The study results provide insights into the global distribution and severity of the burden of digestive system cancers among AYAs. The burden of AYAs with CRC is rapidly increasing worldwide, particularly among males, those aged 30–34, and in high-middle SDI. The disease burden varies across different SDI regions. These findings highlight the need for targeted preventive measures and suggest adjusting CRC screening guidelines.